Searching for the authentic: foodservice at a medieval banquet / Cate Clifford ... [et al.] - Clifford, Cate; Robinson, Richard; Arcodia, Charles (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2009)
Special event research has found that the provision of quality food and beverage services and perceived authenticity are accepted as determinants of visitor satisfaction for special events. Previous work has proposed that these objectives can be aligned to increase both visitor satisfaction and an event's revenue. This paper has two broad aims: to draw on the authenticity literature from several fields of study to develop a broad understanding of the manifestations of food and beverage authenticity vis-à-vis special events, and to apply this conceptualization to an ethnographic study. A participant observation technique was adopted to situate the service of perceived authentic food and beverages within the milieu of various other event authenticity constructs, at a 'staged' Medieval Banquet. It was found that considerable efforts were made to align the food and beverage offerings, and their delivery, with other of the event's authenticity markers. These attempts to authenticate the food and beverage service augmented the overall event. The degree of perceived authenticity at this event derived from complementary authenticating agents and so served to develop a 'unique' authenticity. These agents included notions of impression and image management, the consumption context, and instrumental use of history and association. This paper edges closer to developing a conceptual framework, by which the contribution of food and beverage, and its service, to an event's authenticity might be effectively empirically evaluated.